Identification of Sesame Genomic Variations from Genome Comparison of Landrace and Variety - Wei, Xin; Zhu, Xiaodong; Yu, Jingyin; Wang, Linhai; Zhang, Yanxin; Li, Donghua; Zhou, Rong; Zhang, Xiurong (Frontiers in Plant Science, 2016)
Sesame (Sesamum indicum L.) is one of the main oilseed crops, providing vegetable oil and protein to human. Landrace is the gene source of variety, carrying many desire alleles for genetic improvement. Despite the importance of sesame landrace, genome of sesame landrace remains unexplored and genomic variations between landrace and variety still is not clear. To identify the genomic variations between sesame landrace and variety, two representative sesame landrace accessions, ‘Baizhima’ and ‘Mishuozhima’, were selected and re-sequenced. The genome sequencing and de novo assembling of the two sesame landraces resulted in draft genomes of 267 Mb and 254 Mb, respectively, with the contig N50 more than 47 kb. Totally, 1,332,025 SNPs and 506,245 InDels were identified from the genome of ‘Baizhima’ and ‘Mishuozhima’ by comparison of the genome of a variety ‘Zhongzhi13’. Among the genomic variations, 70,018 SNPs and 8,311 InDels were located in the coding regions of genes. Genomic variations may contribute to variation of sesame agronomic traits such as flowering time, plant height and oil content. The identified genomic variations were successfully used in the QTL mapping and the black pigment synthesis gene, PPO, was found to be the candidate gene of sesame seed coat color. The comprehensively compared genomes of sesame landrace and modern variety produced massive useful genomic information, constituting a powerful tool to support genetic research and molecular breeding of sesame.